MEMBANGUN WEB CRAWLER BERBASIS WEB SERVICE UNTUK DATA CRAWLING PADA WEBSITE GOOGLE PLAY STORE - Ilmawan, Lutfi Budi (ILKOM Jurnal Ilmiah, 2018)
At this time, Google Play Store is not providing API that can be used for accessing datas from applications on itâs application store. With that plenty applicationâs data, it could be used to make it a good research object, specially on data mining field. In this research, the system that is built is the system that can retrieve that applicationsâ data. For multiplatformâs purpose, web services are used for being an interface between client and server. Finally, the built system is working as expected. The system can retrive data from Google Play Store and it is suitable from requirements of data analysis stage. It can also integrated with REST web service to provide multiplatform access.